Testing electron transfer within molecular associates built around anionic C60 and C70 dendrofullerenes and a cationic zinc porphyrin - Sarova, Ginka; Hartnagel, Uwe; Balbinot, Domenico; Sali, Sevda; Jux, Norbert; Hirsch, Andreas; Guldi, Dirk Michael (Chemistry - A European Journal, 2008)
Mono- and bis-functionalized C and C fullerene derivatives (DF, 1-10) that carry one or two oligoanionic dendritic termini in their malonate addends and an oligocationic octapyridinium zinc porphyrin salt (ZnP) were found to self-assemble in buffered aqueous solution to yield a novel series of 1:1 and/or 1:2 electron transfer hybrid associates. Remarkably high association constants-typically on the order of 10 M - were derived that corroborate stable complex formations. A combination of electrostatic and charge-transfer interactions that are operative between the electron-accepting DF and the electron-donating ZnP is considered to contribute to the uniquely high complex stability. First insight into intracomplex excited state interactions came from steady-state and time-resolved fluorescence quenching experiments that were performed with the molecular ZnP/DF hybrid as_sociates. Excited state quenching processes are, for example, evident in form of a bi-exponential fluorescence decay of ZnP - corresponding to a distribution of associated and non-associated ZnP. Unambiguous evidence for an intracomplex electron transfer quenching, namely, formation of ZnP/C and ZnP/C radical ion pairs, was gathered in time-resolved transient absorption measurements. Lifetimes of these radical ion-pairs range from nanoseconds to a few microseconds. © 2008 Wiley-VCH Verlag GmbH & Co. KGaA.